Intravascular Ultrasound–Derived Calcium Score to Predict Stent Expansion in Severely Calcified Lesions. (October 2021) - Zhang, Mingyou; Matsumura, Mitsuaki; Usui, Eisuke; Noguchi, Masahiko; Fujimura, Tatsuhiro; Fall, Khady N.; Zhang, Zixuan; Nazif, Tamim M.; Parikh, Sahil A.; Rabbani, LeRoy E.; Kirtane, Ajay J.; Collins, Michael B.; et al.
Abstract : Background: Coronary calcification inhibits stent expansion. We sought to establish an intravascular ultrasound–derived calcium score to predict stent underexpansion. Methods: This is a retrospective observational study including de novo lesions that underwent intravascular ultrasound–guided stenting and had maximum superficial calcium angle >270°. Lesions with angiographic calcium not treated with atherectomy or scoring/cutting balloon before stent implantation were randomly divided into derivation and validation cohorts. The end point was stent expansion (minimum stent area/average of reference lumen area) at the maximum calcium site, and stent expansion <70% was considered underexpansion. Results: The morphological characteristics associated with stent underexpansion in derivation cohort were (1) superficial calcium angle >270° longer than 5 mm (regression coefficient, −13.0 [95% CI, −18.1 to −7.8], P <0.0001), (2) 360° of superficial calcium (regression coefficient, −14.2 [95% CI, −22.8 to −5.5], P =0.001), (3) calcified nodule (regression coefficient, −8.3 [95% CI, −14.3 to −2.2], P =0.007), and (4) vessel diameter <3.5 mm (regression coefficient, −9.4 [95% CI, −16.0 to −2.7], P =0.006). The calcium score (0-4) was significantly correlated with poor stent expansion (regression coefficient, −8.1 [95% CI, −10.5 to −5.7], P <0.0001) in the validation cohort as well as in the atherectomy cohort (regression coefficient, −4.8 [95% CI, −7.2 to −2.5], P <0.0001) with significant interaction between validation and atherectomy cohorts ( P interaction =0.02). In lesions without angiographic calcium, all calcium severity parameters were less than in the validation cohort, and stent underexpansion was observed in only 1.5% (1/67) of lesions. Conclusions: This intravascular ultrasound calcium score provides the interventionalists with a reliable tool to identify calcified stenoses at risk for stent underexpansion and requiring adjunctive calcium modification before stent implantation. Abstract : Supplemental Digital Content is available in the text.